2016
DOI: 10.18805/ijar.10269
|View full text |Cite
|
Sign up to set email alerts
|

Zinc nanoparticles induced brain lesions and behavioral changesin Tilapia nilotica and Tilapia. zillii

Abstract: In this study, the induced behavioral changes and neuropathology of prolonged exposure to high doses of Zinc nanoparticles (Zn-NPs) in two species of tilapia, T. nilotica and T. zilli. was investigated. Fish that were treated with 2000 µg Zn-NPs/L showed severe degenerative changes and vacuolation in the neuropil, particularly of the optic tectum, with congestion of the blood vessels of both the cerebral cortex and the meninx primitive. Loss of the Purkinje cell layer of the cerebellum was noticed as well. Fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The temperature was maintained at 28 ± 2 °C and dissolved oxygen, at 7.0 ± 0.5 mg L −1 . Fish were fed with a commercial fish diet (Afifi et al, 2016). The daily feed amount was 10% of body weight and the fish were fed 3 times daily.…”
Section: Methodsmentioning
confidence: 99%
“…The temperature was maintained at 28 ± 2 °C and dissolved oxygen, at 7.0 ± 0.5 mg L −1 . Fish were fed with a commercial fish diet (Afifi et al, 2016). The daily feed amount was 10% of body weight and the fish were fed 3 times daily.…”
Section: Methodsmentioning
confidence: 99%
“…Shalaby (2001) also observed depletion in the values of blood parameters in Nile tilapia Oreochromis niloticus due to heavy metal toxicity. Afifi et al, (2016) have observed that prolonged exposure to high doses of Zn nanoparticles probably induces neurotoxicity resulting in neurodegenerative and apopotic lesion in brain of fishes which may cause behavioural changes, a view also supported by Valdiglesias et al, (2013). Kumar et al, (2017) reported that exposure of Clarias batrachus to sub-lethal concentration of Cd and Pb resulted in significant decrease (p < 0.05) in TEC, Hb content and PCV%, while there was a slight increase in case of Cu treatment.…”
Section: Resultsmentioning
confidence: 70%
“…We previously investigated the impacts of Zn-ONPs on O. niloticus and proved the negative impacts of Zn-ONPs' sub-lethal concentration on O. niloticus haematology manifested by the study revealed the presence of normocytic normochromic anaemia, leucocytosis, heterophilia, lymphopenia and monocytopenia and a significant increase in the serum levels of alkaline phosphatase, aminotransferases, urea, creatinine and erythrocytic nuclear and morphological abnormalities along the experimental periods in all treated groups [2]. In other works, the ultrastructure impacts of Zn-ONPs' sub-lethal concentration on O. niloticus gills and the liver were proved [3], and the pathological alterations in gills the liver [11] and the brain [12] were investigated. On the molecular levels, our groups proved the potential impacts of ZnONPs' sub-lethal concentration on O. niloticus antioxidant enzymes' activity and gene expression in the gills and liver [13], muscle [1] and brain [8] manifested by the increase of malondialdehyde, and reduction in glutathione levels, and inhibition of superoxide dismutase (SOD), catalase (CAT), reduced glutathione (GR), glutathione peroxidase (GPx), and glutathione-S-transferase (GST) activities and gene expression.…”
Section: Introductionmentioning
confidence: 94%